Analisis Peningkatan Jalan Dengan Metode Analisis Komponen Pada Jalan Kelurahan Sa’dan Malimbong Kabupaten Toraja Utara - Sesli Rante Payung; Robert Mangontan; Herman Welem Tanje (Paulus Civil Engineering Journal, 2023)
The development of a region/region is certainly supported by the existence of infrastructure constructed to aid in regional growth. Every vehicle that travels on a good road will undoubtedly feel comfortable. Therefore, where roads constitute a crucial component of the community's economic movement and other social activities, maintenance of road conditions is required. This study aims to find out what types, levels and causes of damage occurred on roads in the Sa'dan Malimbong Village, North Toraja Regency. The method used is primary data collection in the field by measuring each type of damage to be analyzed and secondary data in the form of road construction data from The results of this study obtained the types of road damage, namely, crocodile skin cracks, peeling of the surface layer (asphalt), grain release, and holes. Based on the results of the analysis carried out on the 10 road segments studied, it can be concluded that the damage in the Sa'dan Malimbong Village can be repaired by way of overlay or (overlay) with a thickness of 12 cm using Laston.